Post-covid tourisms : virtual tourisms as the new travel trends - Noordeyana Tambi; Mawar Safei; Ermy Azziaty Rozali (Penerbit Universiti Kebangsaan Malaysia, 2022)
This conceptual paper discussed about the COVID-19 pandemic caused many industries to face their downfall, and one of the industries is the tourism industry. As a corollary, a new type of tourism, virtual tourism, is required to promote and restore the tourist sector to its former glory while not dismissing the need for social distancing. Through virtual tourism, people no longer need to travel to a particular tourist destination to experience tourism, but they can now stay at their home and escape to another destination virtually. Aside from giving tourists another level of tourism pleasure, virtual tourism also contributes a lot to the industries such as heritage preservation, tourism marketing, tourism planning and as an opportunity for disabled person to experience tourism. Even though virtual reality technology does not provide the users with enough authentic experience due to the inability to touch the object in the virtual environment, but it can be considered as a good start to advertise virtual tourism as an alternative to conventional tourism especially during the pandemic era where every movement is limited. Keywords: virtual tourism; virtual reality; tourism; heritage; e-Tourism.